2018
DOI: 10.1590/0034-7167-2016-0564
|View full text |Cite
|
Sign up to set email alerts
|

Persistent metabolic syndrome and risk of cardiovascular disease in children and adolescents

Abstract: persistent MetS was associated with obesity, HDL-c and LDL-c, but not with the PDAY score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
1
7
0
7
Order By: Relevance
“…An increase in serum TG level in a MetS patient might be due to resistance to insulin action or insulin deprivation, which was associated with increased lipolysis, intraabdominal fat, which is metabolically very active, releases free fatty acid (FFA) into the portal circulation and the liver converts FFA into triglycerides, which result in high serum TG level. 21,22 This finding was in line with studies reported in India, 33 Iran, 31 Brazil, 34 Malaysia, 35 and Central America; 36 however, this finding is lower than a study reported from Gondar, Ethiopia 56.6%, 37 Hawassa, Ethiopia 68.1%, 38 and Brazil 57.9%, 39 but higher than a report from Iran. 31 The discrepancy in the burden of dyslipidemia might be due to differing cut points in some studies and dietary differences of the study participants.…”
Section: Discussionsupporting
confidence: 81%
“…An increase in serum TG level in a MetS patient might be due to resistance to insulin action or insulin deprivation, which was associated with increased lipolysis, intraabdominal fat, which is metabolically very active, releases free fatty acid (FFA) into the portal circulation and the liver converts FFA into triglycerides, which result in high serum TG level. 21,22 This finding was in line with studies reported in India, 33 Iran, 31 Brazil, 34 Malaysia, 35 and Central America; 36 however, this finding is lower than a study reported from Gondar, Ethiopia 56.6%, 37 Hawassa, Ethiopia 68.1%, 38 and Brazil 57.9%, 39 but higher than a report from Iran. 31 The discrepancy in the burden of dyslipidemia might be due to differing cut points in some studies and dietary differences of the study participants.…”
Section: Discussionsupporting
confidence: 81%
“…Though the most common combination of MS components does not differ by gender, some sex-based differences and an increased number of MS components at early and late/post-puberty were detected. MS is defined by a constellation of physiological, biochemical, clinical and metabolic factors that directly increase the risk of atherosclerosis, type 2 diabetes mellitus (T2DM), and all-cause mortality [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MS) is defined as a cluster of several metabolic factors including obesity, abnormalities in glucose metabolism, hypertension and dyslipidemia, which increase the risk of diabetes mellitus and cardiovascular disease [1,2]. The development of metabolic complication in the pediatric age is directly linked to both excessive weight gain and early onset of obesity [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Neste caso, a paciente é encaminhada à outra unidade, o que se torna inviável para ela, considerada sua rotina pessoal e/ou profissional, além da insegurança de ir à um local novo, com equipe nova, para receber os cuidados numa área íntima. Destaca-se que a paciente que reage desta forma, na maioria das vezes, não recebeu uma orientação adequada e nem acolhimento foi feito da forma correta (CARVALHO et al, 2018;RAMOS et al, 2016).…”
Section: Discussionunclassified